PENGARUH NOMOR RUAS TERHADAP PERTUMBUHAN STEK CABE JAWA (Piper retrofractum Vahl.) - Dhiya Fidha Ramadhanty; Yudi Rinanto (EnviroScienteae, 2022)
Javanese chili (Piper retrofractum Vahl.) is a potential traditional medicine ingredient for Indonesian products which is used as an export commodity to various countries. The increasing demand for Javanese chili must be balanced with increased production through vegetative propagation of cuttings. The purpose of this study was to determine the percentage of survival, the effect of giving Rootone-F growth regulators, and the effect of a different number of cuttings source material on each growth parameter of Javanese chili cuttings. The research design used was a completely randomized design which consisted of 8 groups of cuttings source segments and the administration of a growth regulator Rootone-F in the form of a paste. The results showed that the average percentage of live cuttings, shoot cuttings, and rooted cuttings in all groups of cuttings of Javanese chili plants were classified as successful at 80-85%. Parameters that showed significant differences between treatments were only on the number of roots. The combination of the number of cuttings source segments from the seventh (R7) and eighth (R8) segments with the addition of a growth regulator Rootone-F in the form of a paste showed the highest growth for each parameter compared to the other segment numbers.